Perceived emotional intelligence as a moderator variable between cybervictimization and its emotional impact - Elipe, Paz; Mora-Merchán, Joaquín A.; Ortega-Ruiz, Rosario; Casas, José A. (Frontiers in Psychology, 2015)
The negative effects of traditional bullying and, recently, cyberbullying on victims are well documented, and abundant empirical evidence for it exists. Cybervictimization affects areas such as academic performance, social integration and self-esteem, and causes emotions ranging from anger and sadness to more complex problems such as depression. However, not all victims are equally affected, and the differences seem to be due to certain situational and personal characteristics. The objective of this study is to analyze the relationship between perceived emotional intelligence and the emotional impact of cybervictimization. We hypothesize that emotional intelligence, which has previously been found to play a role in traditional bullying and cyberbullying, may also affect the emotional impact of cyberbullying. The participants in our study were 636 university students from two universities in the south of Spain. Three self-report questionnaires were used: the “European Cyberbullying Intervention Project Questionnaire”, the “Cyberbullying Emotional Impact Scale”; and “Trait Meta-Mood Scale-24”. Structural Equation Models were used to test the relationships between the analyzed variables. The results support the idea that perceived emotional intelligence, by way of a moderator effect, affects the relationship between cybervictimization and emotional impact. Taken together, cybervictimization and perceived emotional intelligence explain much of the variance observed in the emotional impact in general and in the negative dimensions of that impact in particular. Attention and Repair were found to be inversely related to Annoyance and Dejection, and positively related to Invigoration. Clarity has the opposite pattern; a positive relationship with Annoyance and Dejection and an inverse relationship with Invigoration. Various hypothetical explanations of these patterns are discussed.